The impact of CSR interventions on female education development in the rural Niger Delta region of Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
The objective of this investigation was to assess the impact of multinational oil companies' (MOCs) corporate social responsibility (CSR) interventions in female education programmes in the Niger Delta region of Nigeria. A total of 800 rural women were sampled across the region. The results from the logit model showed that rural women depended on CSR interventions of MOCs to address some of the logistical and cultural challenges associated with women's access to post-secondary education in local communities. However, despite the significant success in supporting education initiatives generally, none of the scholarships target females specifically, and compared to men, the low level of human capital in rural women has persisted. This implies that if CSR interventions are not tailored to enhance gender diversity and promote economic opportunities for women alongside education, they may perpetuate the obstruction of women's participation in economic, political and social development. By extension, this could delay the reduction of poverty and attainment of Sustainable Development Goals in the Niger Delta region.
Keywords: J43; O40; O55; Q10; 330; Gender equality; female education; corporate social responsibility; multinationaloil companies; logit model; sub-Saharan Africa